MAGNETIC MOMENT OF THE PROTON FROM KAON PHOTOPRODUCTION UP TO 16 GeV - T. Mart (Jurnal Sains Materi Indonesia, 2003)
MAGNETIC MOMENT OF THE PROTON FROM KAON PHOTOPRODUCTION UP TO 16 GeV. By using the Gerasimov-Drell-Heam (GDH) sum rule and an isobar model of kaon photoproduction, we calculate contributions of kaon-hyperon ﬁnal states to the magnetic moment of the proton and the neutron. We find that the contributions are small. We further extend the isobar model for kaon photoproduction to consider higher energy data by combining the model with a Regge approach. The extended model works nicely between threshold and 16 GeV. We use the model to reﬁne the calculation up to 16 GeV. PACS number(s): 13.60.Le,11.55.Hx, 13.40.Em, 14.20.Dh